Effects of Quercetin Glycoside Supplementation Combined With Low-Intensity Resistance Training on Muscle Quantity and Stiffness: A Randomized, Controlled Trial - Otsuka, Yuta; Miyamoto, Naokazu; Nagai, Akitoshi; Izumo, Takayuki; Nakai, Masaaki; Fukuda, Masahiro; Arimitsu, Takuma; Yamada, Yosuke; Hashimoto, Takeshi (Frontiers in Nutrition, 2022)
Objective: Aging of skeletal muscle is characterized not only by a decrease of muscle quantity, but also by changes in muscle quality, such as an increase in muscle stiffness. The present study aimed to investigate the effects of supplementation with quercetin glycosides (QGs), well-known polyphenolic flavonoids, combined with resistance exercise on muscle quantity and stiffness. Materials and Methods: A randomized, controlled trial was conducted in community-dwelling, Japanese people aged 50-74 years who were randomly allocated to exercise with placebo or 200 mg or 500 mg of QG supplementation. All participants performed low-intensity resistance training mainly targeting thigh muscles with 40% of 1-repetition maximum, 3 days per week for 24 weeks. Muscle cross-sectional area (CSA), lean mass, and vastus lateralis (VL) muscle stiffness were measured before and after the 24-week intervention. Results: Forty-eight subjects completed the 24-week intervention. There were no significant group × time interactions in thigh CSA for primary outcome, as well as lean mass. VL muscle stiffness in the stretched position was significantly lower in both the 200 mg and 500 mg QG groups than in the placebo group after the 24-week intervention (p < 0.05). No significant correlation was observed between changes of VL muscle CSA and stiffness during the 24-week intervention. Conclusions: QG supplementation combined with low-intensity resistance exercise improved passive muscle stiffness independently of muscle quantity. Clinical Trial Registration: UMIN Clinical Trial Registry, UMIN000037633